-9(x)=3

Simple and best practice solution for -9(x)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(x)=3 equation:


-9(x)=3

We simplify the equation to the form, which is simple to understand
-9(x)=3

Reorder the terms in parentheses
+(-9x)=3

Remove unnecessary parentheses
-9x=+3

We move all terms containing x to the left and all other terms to the right.
-9x=+3

We simplify left and right side of the equation.
-9x=+3

We divide both sides of the equation by -9 to get x.
x=-0.33333333333333

See similar equations:

| G=-0.100950783B+-0.2972595078*(-0.3396048918B+-3.36406397G+4.703668862Y)+1.398210291Y | | -0.0722B=0.7152G-Y+0.2126R | | -0.7152G=0.0722B-Y+0.2126R | | -0.2126R=0.7152G+0.0722B-Y | | Y=0.2126R+0.7152G+0.0722B | | y=10-0.667*(15-1.5y-2.5z)-1.667z | | 30=2A+3B+5C | | -12.5+5=x | | w^2+16w^2=c | | 10=2A+3B+5C | | 37x=56+89 | | 54x+18x-12-8x=100 | | 34-5x=7-8x | | 6=2x+20 | | 10x-20=9x+9 | | 24x=72*72-48*48 | | 60x=53*53-37*37 | | 12x=34*34-26*26 | | 23x=68*68-45*45 | | 2x+18=45 | | 12x=50*50-38*38 | | (3a+b)2= | | 6cn-2cn= | | 4x+18x+32=54 | | -2y=1-4x | | 3x=1-4y | | (3x-8)(6x^2-14)=0 | | 6x-9=2m+47 | | 27.8x=2880 | | 5(7+x)-4=-x+1 | | 3[8c+5]= | | y=ln(4x^2) |

Equations solver categories